Investigasi Antesedents Minat Beli Produk Online “Shopee” di Daerah Yogyakarta - Siska Agustin Nurdiana; Albari Albari (CV. Publikasi Indonesia, 2022)
This study aims to examine the effect of viral marketing, e-cosyummer reviews, prices, consumer lifestyles and consumer confidence on consumer buying interest on the shopee application in the area. Yogyakarta. This research uses quantitative methods. The population used in this study is all people who buy products on the Shopee application who are domiciled in the Yogyakarta area. The sampling technique used in this research is convenience sampling. Based on the results of descriptive analysis, the highest average score on the viral marketing variable is based on three indicators, namely the existence of promos and discounts sent to consumers, information that is easy to understand and spreading information through the comments column. The results of this study succeeded in showing 12 proven hypotheses. Based on the results of descriptive analysis, the highest average score on the viral marketing variable is found in three indicators, namely the existence of promos and discounts sent to consumers, information that is easy to understand and spreading information through the comments column.